Focused Ultrasound Hyperthermia Augments Release of Glioma-derived Extracellular Vesicles with Differential Immunomodulatory Capacity - Sheybani, Natasha D. (Theranostics, 2020)
Background: Increasing evidence points to the critical role of extracellular vesicles (EVs) as molecular parcels that carry a diverse array of bioactive payloads for coordination of complex intracellular signaling. Focused ultrasound (FUS) hyperthermia is a technique for non-invasive, non-ionizing sublethal heating of cells in a near-instantaneous manner; while it has been shown to improve drug delivery and immunological recognition of tumors, its impact on EVs has not been explored to date. The goal of this study was to determine whether FUS impacts the release, proteomic profile, and immune-activating properties of tumor-derived EVs. Methods: Monolayered murine glioma cells were seeded within acoustically transparent cell culture chambers, and FUS hyperthermia was applied to achieve complete coverage of the chamber. Glioma-derived EVs (GEVs) were isolated for characterization by Nanoparticle Tracking Analysis, cryo-electron microscopy and mass spectrometry. An in vitro experimental setup was designed to further dissect the impact of GEVs on innate inflammation; immortalized murine dendritic cells (DCs) were pulsed with GEVs (either naïve or FUS hyperthermia-exposed) and assayed for production of IL-12p70, an important regulator of DC maturation and T helper cell polarization toward the interferon-γ-producing type 1 phenotype. Results: We confirmed that FUS hyperthermia significantly augments GEV release (by ~46%) as well as shifts the proteomic profile of these GEVs. Such shifts included enrichment of common EV-associated markers, downregulation of markers associated with cancer progression and resistance and modulation of inflammation-associated markers. When DCs were pulsed with GEVs, we noted that naïve GEVs suppressed IL-12p70 production by DCs in a GEV dose-dependent manner. In contrast, GEVs from cells exposed to FUS hyperthermia promoted a significant upregulation in IL-12p70 production by DCs, consistent with a pro-inflammatory stimulus. Conclusion: FUS hyperthermia triggers release of proteomically distinct GEVs that are capable of facilitating an important component of innate immune activation, lending both to a potential mechanism by which FUS interfaces with the tumor-immune landscape and to a role for GEV-associated biomarkers in monitoring response to FUS.